Applying Human Factors Engineering Program to the Modernization Project of NPP Control Room in accordance with U.S.NRC and KTA Regulations - Renato Koga de Avellar; Roberto Schirru (Brazilian Journal of Radiation Sciences, 2019)
Application of Human Factors Engineering (HFE) in the design and implementation of such a project is essential to ensure that the new man-machine interface outcoming from the modernization does not have any negative impacts on human performance and plant safety.